VD_FINDINFO HC / 2022 / 763 vom 3. Oktober 2022 - VD Tribunal cantonal (2022)
ENFANT, CONJOINT, PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, REVENU HYPOTHÉTIQUE, DÉBUT | 173 al. 3 CC, 176 al. 1 CC, 176 al. 3 CC, 276 al. 1 CC, 276 al. 2 CC, 285 al. 1 CC, 285 al. 2 CC, 129 CPC (CH), 276 al. 1 CPC (CH)